PENGARUH MOTIVASI KERJA, PELATIHAN DAN KEPUASAN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR KECAMATAN MAJAULENG KABUPATEN WAJO - Andi Ardasanti (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2019)
Work motivation, training and job satisfaction towards Employee Work Achievement at Majauleng District Office in Wajo Regency, both partially and simultaneously. This study uses a survey research design model that uses correlational using a quantitative approach. Correlational research discusses explaining that there is no relationship or relationship between various variables based on the size of the coefficient in question. The population in this study were all employees at the Majauleng District Office in Wajo District as many as 72 employees. Sampling of this study was carried out using saturated samples or census techniques, namely all populations were made as samples. Quantitative data analysis techniques obtained from the results of questionnaires using multiple linear regression analysis (multiple regression analysis). The results showed that partially simultaneous, motivation, training and positive job satisfaction were significant and significant for employee work performance at Majauleng District Office, Wajo District.